Design of industrial information systems - Boucher, Thomas O. (Elsevier, 2006)
Design of Industrial Information Systems presents a body of knowledge applicable to many aspects of industrial and manufacturing systems. New software systems, such as Enterprise Resource Planning, and new hardware technologies, such as RFID, have made it possible to integrate what were separate IT databases and operations into one system to realize the greatest possible operational efficiencies. This text provides a background in, and an introduction to, the relevant information technologies and shows how they are used to model and implement integrated IT systems. With the growth of courses in information technology offered in industrial engineering and engineering management programs, the authors have written this book to show how such computer-based knowledge systems are designed and used in modern manufacturing and industrial companies. Introduces Data Modeling and Functional Architecture Design, with a focus on integration for overall system design Encompasses hands-on approach, employing many in-chapter exercises and end-of-chapter problem sets with case studies in manufacturing and service industries Shows the reader how Information Systems can be integrated into a wider E-business/Web-Enabled Database business model Offers applications in Enterprise Resource Planning (ERP) and Manufacturing Execution Systems (MES), with an accompanying website containing usable sample databases.